Simbiolisme Akulturatif dan Toleransi Umat Hindu-Islam : Analisis Interaksionisme Simbolik pada Upacara Unan-Unan Wilayah Tengger di Tosari - Salsa Putri Ismaul Khotimah; Nikmah Suryandari (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2025)
This study examines acculturative symbolism and interfaith tolerance through the implementation of the Unan-Unan Ceremony in Tosari District, Tengger region, using a qualitative case study approach and Herbert Blumer's symbolic interactionism theory as an analytical tool. The Unan-Unan tradition, as a sacred five-year ritual of the Tengger Hindu community, not only carries spiritual meanings such as warding off evil and purifying nature but also serves as a space for social interaction actively involving the Muslim community, particularly in social, cultural, and logistical aspects. Cultural symbols such as offerings, mantras, and collective prayers are interpreted as the result of negotiations and the formation of cross-religious collective identity. The research findings indicate that the symbolism in this tradition represents values of tolerance, mutual aid, and teposliro, thereby strengthening an inclusive and harmonious social structure within a multicultural society. The Unan-Unan ceremony serves as tangible evidence that a cultural approach can create spaces for tolerance and harmony among religious groups without erasing their respective identities. Thus, this tradition is not only significant as a cultural heritage but also as a model of diversity and social peace in Indonesia.